THE IMPACT OF IMPROPERLY ILLUMINATED WORK ENVIRONMENTS ON HUMAN NERVOUS SYSTEM ACTIVITY AND VISUAL ACUITY (World Bulletin of Public Health, 2025)
This scientific article analyzes the impact of improperly illuminated work environments on human health, particularly on nervous system activity and visual acuity. Lighting level is one of the key factors of occupational hygiene, and insufficient illumination can lead to cognitive fatigue, visual strain, stress, and neurophysiological dysfunction. The article examines visual fatigue caused by inadequate illumination, disturbances of the melatonin rhythm, and declines in brain activity. Based on the abstract, the article is structured in alignment with SanPiN, EN 12464-1, and WHO recommendations.
Keywords: Lighting; nervous system; visual acuity